Analysis of the Implementation of Training and Development Programs in Enhancing Employee Competence at the Office of the Ministry of Religious Affairs of Surabaya City - Risfi Asfiana; Hidayatul Wafiyyah; Dannis Nur Ramadhani (Maddah: Journal of Advanced Da'wah Management Research, 2026)
This study is grounded in the increasing importance of human resource development in public institutions, particularly through training and development programs aimed at enhancing employee competencies. Effective implementation of such programs is essential to improve productivity, professionalism, and organizational performance. Therefore, this study aims to analyze and evaluate the implementation of training and development programs in improving employee competencies at the Office of the Ministry of Religious Affairs in Surabaya. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews with key informants, including the Head of the Hajj and Umrah Division (PHU) and the Personnel Sub-Coordinator. The data were analyzed using a thematic analysis technique to identify patterns related to program implementation and its outcomes. The results indicate that structured and continuous training programs have successfully enhanced employees’ skills, knowledge, and work attitudes, leading to improved productivity and professionalism. However, several challenges were identified, including limited dissemination of training outcomes, time constraints, and suboptimal scheduling. This study concludes that optimizing training management is crucial to achieving more effective and sustainable human resource development.